The sanctuary of Thermos and the origins of Aetolia - Álvarez Soria, Ignacio Jesús (ARYS. Antigüedad: Religiones y Sociedades, 2021)
The rural sanctuary of Thermos in Aetolia was the political centre of the Aetolian state and the confederation associated with it. A fact that decisively marked the political structure and the territorial configuration of Aetolia, as well as the nature of the social organization that we find in the area. This paper will analyse the geographical, economic and symbolic factors that led to Thermos becoming a sort of capital of the Aetolians, emphasising its status as a sacred place.
Keywords: Aetolia; aristocracy; festival; husbandry; megaron; sanctuary; Thermos